1988
DOI: 10.3758/bf03213485
|View full text |Cite
|
Sign up to set email alerts
|

The crossword puzzle paradigm: The effectiveness of different word fragments as cues for the retrieval of words

Abstract: We investigated the internal structure of words in the mental lexicon by using a crossword puzzle paradigm. In two experiments, subjects were presented with word fragments along with a semantic cue, and were asked to retrieve the whole word that contained the presented fragment and was compatible with the semantic information. In Experiment 1, we found that any cluster of three adjacent letters facilitated retrieval better than dispersed letters. Moreover, syllabic clusters had a greater facilitative effect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 16 publications
2
25
1
Order By: Relevance
“…A weakness in their study was that the syllabic clues were invariably the stressed syllables of the target words, so the phonological-morphological distinction was confounded with pronunciation stress. Goldblum and Frost (1988) considered their results to be consistent with the assumption that word recognition is mediated, at least sometimes, by syllable recognition. Letter recognizers are connected directly to word recognizers, but also to syllable recognizers that are, in turn, connected to word recognizers and can therefore facilitate the word recognition process.…”
Section: Structural Cluessupporting
confidence: 68%
See 4 more Smart Citations
“…A weakness in their study was that the syllabic clues were invariably the stressed syllables of the target words, so the phonological-morphological distinction was confounded with pronunciation stress. Goldblum and Frost (1988) considered their results to be consistent with the assumption that word recognition is mediated, at least sometimes, by syllable recognition. Letter recognizers are connected directly to word recognizers, but also to syllable recognizers that are, in turn, connected to word recognizers and can therefore facilitate the word recognition process.…”
Section: Structural Cluessupporting
confidence: 68%
“…In an experimental comparison of the effectiveness of the four kinds of clues distinguished here, Goldblum and Frost (1988) found syllabic fragments to be superior to all the other types of letter combinations, and any cluster of adjacent letters to be better than the same number of nonadjacent letters. In a second experiment, these investigators found syllabic clues to be superior to comparable morphemic-unit clues (e.g., _ _NOT_ _ _ _ _ vs. _ _ _ _TON_ _ _ as clues for MONOTONOUS).…”
Section: Structural Cluesmentioning
confidence: 99%
See 3 more Smart Citations